10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
PTCD should be considered in children with developmental delay and sensorineural hearing loss. MRI is crucial for identifying the characteristic dorsal "tegmental cap" and associated hindbrain anomalies. Vestibulocochlear nerve aplasia may explain severe hearing impairment in PTCD. Early diagnosis enables timely multidisciplinary rehabilitation and audiological intervention.